Decision support system for determining chili land using weighted product method - Ramadiani Ramadiani; Bayu Ramadhani; Zainal Arifin; Muhammad Labib Jundillah; Azainil Azainil (Institute of Advanced Engineering and Science, 2020)
Chili is one of the most consumed food commodities in Indonesia. Thus, chili is very influential to the economic, also inflation and deflation of an area. In order for the needs of chili to be fulfilled and to be able to export, the production must be increased with one consideration being the selection of the right land. The right land must meet the criteria agreed upon by experts, there is land height, soil pH, nutrient value and ambient temperature. This research aims to create a system to support the decision of chili crop land selection using the weighted product method. By entering land data according to the criteria, the user can easily find out which land has the potential to have a higher suitability for chili plants. The result of this system is in the form of land ranking that can help users decide which land to use for chili cultivation.